The New Frontier of Exploitation: Human Trafficking for Online Scams in Taiwan - Michael, Sheila Devi (INTERNATIONAL JOURNAL OF CHINA STUDIES, 2025)
Human trafficking in Taiwan has taken on new dimensions with the rise of technology-driven crimes. In 2022 alone, hundreds of Taiwanese victims were rescued from trafficking syndicates that exploited them in online scamming networks operating both within Taiwan and across Asia. Victims of other nationalities have also been found trapped in Taiwan’s scam industries, highlighting the country’s dual role as a source and destination for trafficking. This shift demonstrates that trafficking no longer revolves solely around forced labour or sexual exploitation but increasingly involves coercion into digital fraud, a criminal economy generating trillions of dollars globally. The significance of this study lies in situating Taiwan at the centre of an evolving global trafficking trend, where online scams represent a new frontier of exploitation with profound security, legal, and human rights implications. Accordingly, this paper has three objectives: to explore the operations of human trafficking in Taiwan for online scams; to examine the challenges faced by the Taiwanese government in combating these crimes; and to analyse the government’s responses in combating human trafficking for online scamming.